2015
DOI: 10.12705/644.2
|View full text |Cite
|
Sign up to set email alerts
|

Towards resolving phylogenetic relationships in the Ficinia clade and description of the new genus Afroscirpoides (Cyperaceae: Cypereae)

Abstract: Cyperaceae is the third‐largest family of monocotyledons and one of the 10 largest families of angiosperms. The family includes two subfamilies and several tribes, one of which, Cypereae, is the aim of the present study. Recent studies recognize the Ficinia clade, composed of six genera (Dracoscirpoides, Erioscirpus, Ficinia, Hellmuthia, Isolepis, Scirpoides), as more closely related to Cyperus (Cypereae) than to Scirpus (Scirpeae), where it was traditionally placed. In this study, phylogenetic analyses of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 46 publications
(77 reference statements)
6
17
0
Order By: Relevance
“…now consists of approximately 18 species (Novoselova, 1994b;Ball & Wujek, 2002;Léveillé-Bourret & Starr, in press) with E. transiens an aberrant oddity characterised by spikelets arranged into an anthela of dense, globose heads with branches subtended by extremely long bracts and flowers with bristles fused at the base. This type of inflorescence suggests E. transiens is distantly related to Eriophorum and more likely to be allied to elements in the Ficinia Clade as analyses have shown for other recent Scirpus segregates (e.g., Afroscirpoides and Dracoscirpoides; Muasya et al, 2012;García-Madrid et al, 2015). The taxonomy and relationships of E. transiens are currently under study.…”
Section: Conservation Status and Species Distributionmentioning
confidence: 74%
See 2 more Smart Citations
“…now consists of approximately 18 species (Novoselova, 1994b;Ball & Wujek, 2002;Léveillé-Bourret & Starr, in press) with E. transiens an aberrant oddity characterised by spikelets arranged into an anthela of dense, globose heads with branches subtended by extremely long bracts and flowers with bristles fused at the base. This type of inflorescence suggests E. transiens is distantly related to Eriophorum and more likely to be allied to elements in the Ficinia Clade as analyses have shown for other recent Scirpus segregates (e.g., Afroscirpoides and Dracoscirpoides; Muasya et al, 2012;García-Madrid et al, 2015). The taxonomy and relationships of E. transiens are currently under study.…”
Section: Conservation Status and Species Distributionmentioning
confidence: 74%
“…The modern circumscription of Scirpus, which is based on multiple lines of evidence from embryo types (van der Veken, 1965), fruit epidermal silica bodies (Schuyler, 1971) inflorescence structure (Bruhl, 1995;Goetghebeur, 1986Goetghebeur, , 1998 and molecular phylogeny (Muasya et al, 2009;Muasya et al, 2000), has considerably narrowed the problem. Recent studies have consistently demonstrated that morphologically confusing Scirpus or Eriophorum species were typically separate generic lineages related to either species in the distantly related Ficinia Clade of Cypereae (Muasya et al, 2012;Yano et al, 2012;García-Madrid et al, 2015), or closely allied to Scirpus and Eriophorum within the SCC, a cosmopolitan group comprising eight major lineages (Dulichieae, Khaosokia, Calliscirpus, Sumatroscirpeae, Cariceae, Trichophorum Clade, Zameioscirpus Clade, and Scirpus+Eriophorum Clade; Dhooge, Goetghebeur & Muasya, 2003;Gilmour, Starr & Naczi, 2013;Léveillé-Bourret et al, 2015;Semmouri et al, 2019). Several of these lineages were clearly separate from Scirpus and Eriophorum and their allies in tribe Scirpeae, such as tribes Cariceae, Dulichieae and Sumatroscirpeae, and the morphologically unusual genus Khaosokia, but the relationships of the remaining elements were not clear because the limits of Scirpus and Eriophorum remained ill-defined.…”
Section: Conservation Status and Species Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modern circumscription of Scirpus , which is based on multiple lines of evidence from embryo types (Van der Veken, 1965), fruit epidermal silica bodies (Schuyler, 1971) inflorescence structure (Bruhl, 1995; Goetghebeur, 1986; Goetghebeur, 1998) and molecular phylogeny (Muasya et al, 2009; Muasya et al, 2000), has considerably narrowed the problem. Recent studies have consistently demonstrated that morphologically confusing Scirpus or Eriophorum species were typically separate generic lineages related to either species in the distantly related Ficinia Clade of Cypereae (Muasya et al, 2012; Yano et al, 2012; García-Madrid et al, 2015), or closely allied to Scirpus and Eriophorum within the SCC, a cosmopolitan group comprising eight major lineages (Dulichieae, Khaosokia , Calliscirpus , Sumatroscirpeae, Cariceae, Trichophorum Clade, Zameioscirpus Clade, and Scirpus+Eriophorum Clade; Dhooge, Goetghebeur & Muasya, 2003; Gilmour, Starr & Naczi, 2013; Léveillé-Bourret et al, 2015; Léveillé-Bourret, Starr & Ford, 2018; Semmouri et al, 2019). Several of these lineages were clearly separate from Scirpus and Eriophorum and their allies in tribe Scirpeae, such as tribes Cariceae, Dulichieae and Sumatroscirpeae, and the morphologically unusual genus Khaosokia , but the relationships of the remaining elements were not clear because the limits of Scirpus and Eriophorum remained ill-defined.…”
Section: Discussionmentioning
confidence: 99%
“…As family relationships became ever clearer, the most problematic taxa blurring their limits were slowly eliminated such that a focus on an even narrower range of taxa was possible. Studies demonstrated that morphologically confusing species of Scirpus or Eriophorum were separate generic lineages related either to elements in the distantly related Ficinia Clade of tribe Cypereae (Muasya et al, 2012; Yano et al, 2012; García-Madrid et al, 2015), or closely allied to Scirpus and Eriophorum within the Scirpo-Caricoid Clade or “SCC” (i.e., the Cariceae-Dulichieae-Scirpeae Clade, renamed for recent changes in tribal classification; Léveillé-Bourret, Starr & Ford, 2018; Léveillé-Bourret & Starr, 2019), a cosmopolitan group of more than 2,250 species and eight major lineages (Dulichieae, Khaosokia , Calliscirpus , Cariceae, Sumatroscirpeae, Trichophorum Clade, Zameioscirpus Clade, and Scirpus+Eriophorum Clade; Dhooge, Goetghebeur & Muasya, 2003; Gilmour, Starr & Naczi, 2013; Léveillé-Bourret et al, 2015; Semmouri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%